Effect of the carbohydrates composition on physicochemical parameters and metabolic activity of starter culture in yogurts - Vénica, Claudia Inés (2018)
The carbohydrate composition of the milk base plays a crucial role in the fermentation process of yogurt. In this study we investigate the effect of the traditional (TRAD) and delactosed (DEL) milks, added or not sucrose (S) in yogurt making, on the physicochemical parameters, growth of cultures and the formation of organic acids and volatile compounds during fermentation and storage. Yogurts made with delactosed milk had a delay in the fermentation up to 30 min in reaching the final pH and a slight minor postacidification, in comparison to yogurts prepared from traditional milk. Sucrose addition decreased the fermentation time in delactosed products. These observations were not accompanied by a significant change in the counts of thermophilic streptococci and thermophilic lactobacilli bacteria. The most notable differences in volatile compounds profiles were recorded in DEL + S respect to the remaining yogurts. The highest levels of diacetyl, 2,3-pentanedione, ethanol and ethyl esters found in DEL + S yogurts could be correlated with the higher glucose content, the main precursor of these compounds.